Treatment of Intestinal Parasitic Infections in Elderly and Mentally Retarded Patients - Sima Rasti; Mansoreh Momen Heravi; Sahar Salageghe (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The rate of person to person transmission of intestinal parasites is high in elderly and mentally retarded patients and lack of treatment may cause disease spread.This sudy was conducted to evaluate the efficacy of treatment of intestinal parasitic infections in elderly and mentallyretardedpatients of Golabchi center of Kashan. Methods & Materials: This descriptive study was carried out on 133 elderly and mentallyretardedpatients of Golabchi center of Kashan in 2007. Infected participants were treated according to the stool examination and scotch tape results. These tests were performedagain after one month and response to treatment wasdetermined. A questionnaire was completed during interview with patients to obtain the data of sex and age,clinical symptoms and side effects of drugs. Descriptive data analysis was performed to evaluate the results. Results: In general, 64.7% of patients were male and the rate of response to treatment was 93.2%. The response rate was highest (79.5%) and lowest (26.7%) in patients with <30 and >70 years of age respectively. Besides, theresponse rate was 93.6%, 89.2%, 90% and 100% in oxyur, entamoeba histolytica, giardia lamblia anddientamoeba fragilis respectively. Conclusion: With regardsto the high rate of response to treatment,resistance to routin anti parasitic drugs seems unlikely. The lack of response to tratment can be either dut to high severity of the infection or due to incorrect using of drugs.